2017
DOI: 10.1155/2017/3419801
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Application of Inorganic Solidified Foam Filling Material for Coal Mines

Abstract: Spontaneous combustion of residual coal in a gob due to air leakage poses a major risk to mining safety. Building an airtight wall is an effective measure for controlling air leakage. A new type of inorganic solidified foam-filled material was developed and its physical and chemical properties were analyzed experimentally. The compressive strength of this material increased with the amount of sulphoaluminate cement. With an increasing water-cement ratio, the initial setting time was gradually extended while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Apart from being used in the traditional building elds, FLA has been applied in di erent areas as a good raw material for the preparation of geopolymer [8][9][10][11][12]. For example, to prove the possibility of in-situ resource utilization of FLA, there are a good many scholars having done plenty of basic studies on this aspect [13][14][15], among which there is one proposing that y ash foamed geopolymer (FAFG) as back lling material can be an excellent combination of y ash consumption and coal mine re prevention [16,17]. e complex underground environment demands highly for some speci c properties of FAFG, mainly focusing on its pore structure and strength.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being used in the traditional building elds, FLA has been applied in di erent areas as a good raw material for the preparation of geopolymer [8][9][10][11][12]. For example, to prove the possibility of in-situ resource utilization of FLA, there are a good many scholars having done plenty of basic studies on this aspect [13][14][15], among which there is one proposing that y ash foamed geopolymer (FAFG) as back lling material can be an excellent combination of y ash consumption and coal mine re prevention [16,17]. e complex underground environment demands highly for some speci c properties of FAFG, mainly focusing on its pore structure and strength.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, under the same conditions, the longer the curing time, the greater the compressive strength owing to the more stable crystal structure of the hydration product [30]. is was because the higher the foam dosage, the higher the bubble rate of the solidified foam cement, the better the compressibility, and the greater the yield strength [39].…”
Section: Effect Of Foam Dosage On Compressive Strength Of Thementioning
confidence: 89%
“…Finally, the foam slurry was poured into the mold to prepare the foamed cement module (100 × 100 × 100 mm). Studies have shown that the strength of the cured foam cement is higher when the water-cement mass ratio is approximately 0.5 [30]. erefore, the water-cement ratio used in this study was 0.5. e foam and gel slurry were mixed in a volume ratio.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Because of their long solidification times, low foam expansion rates, and poor resistance to dynamic pressure, these materials cannot be used extensively in deep coal mines. To overcome these shortcomings, Wen et al [20] and Tan et al [21] developed a type of inorganic solidified foamfilling material and analyzed the effects of constituent materials on its basic physical and chemical properties in various experiments. Jambor [22] and Tang [23] probed the effects of pore structure on the FC strength.…”
Section: Introductionmentioning
confidence: 99%